2021
DOI: 10.1021/acs.jafc.0c06106
|View full text |Cite
|
Sign up to set email alerts
|

Study on the Biocontrol Potential of Antifungal Peptides Produced by Bacillus velezensis against Fusarium solani That Infects the Passion Fruit Passiflora edulis

Abstract: A bacterium identified as Bacillus velezensis with a growth inhibitory effect against Fusarium solani, a pathogen that caused basal stem rot in the passion fruit Passiflora edulis, was isolated in this study. From the fermentation broth of B. velezensis, a type of antifungal peptide (named BVAP) with a molecular weight of ca. 1.5 kDa was purified and found to be fengycin. BVAP suppressed mycelial growth in F. solani with an IC50 of 5.58 μg/mL, which was superior to those of the chemical fungicides thiram (41.2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 50 publications
1
20
0
Order By: Relevance
“…Besides, W1 showed higher tolerance to a variety of proteases against F. oxysporum . These characteristics were better than the antifungal peptides produced by B. amyloliquefaciens S185, PT14, and B. velezensis HNAH 17806 ( Kim et al, 2015 ; Singh et al, 2021 ; Wang et al, 2021 ), indicating that W1 has superior application potential in the biocontrol of plant diseases.…”
Section: Discussionmentioning
confidence: 97%
“…Besides, W1 showed higher tolerance to a variety of proteases against F. oxysporum . These characteristics were better than the antifungal peptides produced by B. amyloliquefaciens S185, PT14, and B. velezensis HNAH 17806 ( Kim et al, 2015 ; Singh et al, 2021 ; Wang et al, 2021 ), indicating that W1 has superior application potential in the biocontrol of plant diseases.…”
Section: Discussionmentioning
confidence: 97%
“…citri (Etchegaray et al 2008 ). Fengycin from Bacillus velezensis achieved better inhibition of mycelial growth in Fusarium solani than chemical fungicides, and its activity remained stable even at high temperatures and low pH values (Wang et al 2021 ). Rahnella aquatilis JZ-GX1 produces volatile gases that antagonize Colletotrichum gloeosporioides , which causes Liriodendron chinense × tulipifera black spot, by containing 3-methyl-1-butanol and 2-methyl phenyl ether ethyl ether (Kong et al 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…A recent study indicated that B. velezensis effectively prevented F. solani infection in passion fruits ( Wang et al, 2021 ). B. velezensis strains with secondary-metabolite-secretion ability could inhibit F. solani and oomycetes, and these strains were reported to serve plant growth–promoting rhizobacteria ( Cheffi et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%